A white high thermal conductivity para-aramid fiber and preparation method thereof

By dispersing hexagonal boron nitride in concentrated sulfuric acid and mixing it with polyterephthalyl paraphenylamidine, white high thermal conductivity para-aramid fiber was prepared, and the failure to develop white high thermal conductivity para-aramid fiber in the prior art was solved. The problem of ion fiber achieves the requirements of thermal conductivity and appearance color, and improves the strength and color fastness of the fiber.

CN118854479BActive Publication Date: 2025-01-10TAYHO ADVANCED MATERIALS GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411364396.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-10
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The prior art has failed to develop white high thermal para-aramid fibers, which cannot meet the needs of electronic and electrical equipment for thermal conductivity and appearance color.

Method used

Hexagonal boron nitride is dispersed in concentrated sulfuric acid, mixed with polyterephthalyl paraphenylamidine, and white highly thermally conductive paraaramid fiber is prepared through spinning process, using hexagonal boron nitride as a thermally conductive filler Also used as a white pigment.

Benefits of technology

The preparation of white high thermal conductivity para-aramid fiber is realized, which meets the needs of thermal conductivity and appearance color, and at the same time improves the strength and color fastness of the fiber, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of aramid fiber preparation methods, and in particular to a white high thermal conductivity para-aramid fiber and a preparation method thereof, wherein the preparation method comprises the following steps: (1) dispersing hexagonal boron nitride powder in concentrated sulfuric acid to obtain a hexagonal boron nitride dispersion, wherein the weight ratio of the hexagonal boron nitride powder to the concentrated sulfuric acid is 1:(15-300), the particle size of the hexagonal boron nitride powder is 100-1000nm, and the concentration of the concentrated sulfuric acid is not less than 99.8% by mass; (2) dissolving poly(p-phenylene terephthalamide) in the hexagonal boron nitride dispersion to obtain a spinning solution, wherein the weight ratio of the poly(p-phenylene terephthalamide) to the hexagonal boron nitride dispersion is 1:(3.9-4.3); (3) filtering and degassing the spinning solution, spinning by a dry-jet wet spinning method, alkali washing, water washing, drying, and oiling to obtain a white high thermal conductivity para-aramid fiber. The para-aramid fiber has a white appearance and high thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a white high-thermal-conductivity para-aramid fiber and a preparation method thereof, belonging to the technical field of aramid fiber preparation methods. Background Art

[0002] Para-aramid has a rigid rod-shaped molecular structure and highly oriented molecular chains, so it has high strength, high modulus, high temperature resistance, chemical corrosion resistance, fatigue resistance and other advantages, and its comprehensive performance is very excellent. The application of para-aramid is mainly concentrated in the fields of bulletproof protection, optical fiber reinforcement, rubber reinforcement and composite materials.

[0003] The color of para-aramid fiber itself is yellow, but with the expansion of the application scope of para-aramid fiber and its similar and downstream products in the world's chemical fiber reinforcement materials, colored para-aramid products have appeared on the market. According to market feedback and relevant information, colored para-aramid is currently mainly used in the fields of protection and consumer electronics. There are para-aramid colored yarns in bright black, bright red, military green and other colors. There are no white para-aramid products on the market. This is mainly because the most commonly used white colorants, titanium dioxide and other white pigments, are not resistant to sulfuric acid.

[0004] For example, Chinese patent application CN113882030A discloses a method for preparing colored para-aramid fiber and its fiber product, comprising: (1) pre-treating dye particles; (2) mixing the dye particles pre-treated in step (1) with aramid slurry and spinning to obtain spun fibers; (3) secondary dyeing the spun fibers, wherein the pre-treatment in step (1) includes recrystallization of the dye particles; however, the colored para-aramid fibers prepared in this patent are black, navy blue or military green in color. Chinese patent application CN110359115A discloses a method for preparing colored para-aramid fiber, comprising the following steps: drying and grinding the dye particles, and then adding them to a coagulation bath for dissolution and dispersion; preparing a coagulation bath solution, wherein the coagulation bath solution comprises a 5-20% dilute sulfuric acid aqueous solution; filtering and degassing the para-aramid spinning stock solution, and then spinning it by dry-jet wet spinning, and then placing the spun nascent fiber into a coagulation bath for dyeing; after dyeing, alkali washing, water washing, drying, and heat treatment of the colored para-aramid fiber to obtain a finished colored para-aramid fiber; the colored para-aramid fiber prepared by this method is black, red, and orange. Currently, there is no method for preparing white para-aramid fiber.

[0005] In addition, when para-aramid fiber products are used in electronic and electrical equipment, such as mobile phone cases, mobile phone back panels, wearable electronic device housings and other products, there is a higher demand for its thermal conductivity. Improving the thermal conductivity of para-aramid can help electronic products dissipate the heat generated during use in a timely manner, avoiding equipment failure caused by excessive temperature. At present, white para-aramid fiber and high thermal conductivity para-aramid fiber have not been reported, so it is of great value to develop a white high thermal conductivity para-aramid fiber. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a white high thermal conductivity para-aramid fiber and a preparation method thereof, which can meet the appearance requirements of downstream applications for white para-aramid fibers and also meet the high thermal conductivity requirements of electronic and electrical equipment for para-aramid products.

[0007] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing white high thermal conductivity para-aramid fiber, the preparation method comprising:

[0008] S1, dispersing hexagonal boron nitride in concentrated sulfuric acid to obtain a hexagonal boron nitride dispersion;

[0009] S2, dissolving poly(p-phenylene terephthalamide) in a hexagonal boron nitride dispersion to obtain a spinning solution;

[0010] S3, filtering and degassing the spinning solution, and then obtaining white high thermal conductivity para-aramid fiber through a spinning process.

[0011] Furthermore, the particle size of the hexagonal boron nitride is 100-1000 nm.

[0012] Preferably, the particle size of the hexagonal boron nitride is 500-700 nm.

[0013] Furthermore, in step S1, the weight ratio of the hexagonal boron nitride to the concentrated sulfuric acid is 1:(15-300); and the mass concentration of the concentrated sulfuric acid is not less than 99.8%.

[0014] Preferably, in step S1, the weight ratio of hexagonal boron nitride to concentrated sulfuric acid is 1:(20-100).

[0015] Furthermore, the weight ratio of the poly(p-phenylene terephthalamide) to the hexagonal boron nitride dispersion is 1:(3.9-4.3).

[0016] Furthermore, hexagonal boron nitride is dispersed in concentrated sulfuric acid by a high-speed shear emulsifier, the speed of the high-speed shear emulsifier is 2000-3000rpm, the emulsification time is 2-5h, and immediately after emulsification, poly(p-phenylene terephthalamide) and hexagonal boron nitride dispersion are mixed by a twin-screw extruder to obtain a spinning solution.

[0017] Furthermore, the specific process of step S3 is: filtering and degassing the spinning solution, extruding it through a spinneret for dry-jet wet spinning, alkali washing, water washing, drying, and oiling to obtain white high thermal conductivity para-aramid fiber.

[0018] The invention also discloses a white para-aramid fiber with high thermal conductivity. The white para-aramid fiber with high thermal conductivity is prepared by adopting the preparation method of the invention.

[0019] Furthermore, the monofilament fineness of the white high thermal conductivity para-aramid fiber is 1.5D, the multifilament linear density is 400-3000D, and the thermal conductivity along the fiber axis is above 0.1 W / (m·K).

[0020] The beneficial effects of the present invention are:

[0021] In the process of preparing para-aramid fiber, the present invention introduces hexagonal boron nitride into concentrated sulfuric acid. The hexagonal boron nitride powder is used as a thermal conductive filler and also as a white pigment, which improves the thermal conductivity of the para-aramid fiber and satisfies the downstream customers' demand for the appearance of white para-aramid fiber products, expands the downstream application of the para-aramid fiber, and the white high thermal conductivity para-aramid fiber has good color fastness and strength performance; and the preparation method is simple and suitable for application in industrial production.

[0022] In the preparation method of the white high thermal conductivity para-aramid fiber of the present invention, by selecting hexagonal boron nitride powder with a suitable particle size and controlling the operating conditions in the process, the entire spinning process can be carried out smoothly, and finally the para-aramid fiber with excellent thermal conductivity, good strength performance, high color fastness and white appearance is obtained. DETAILED DESCRIPTION

[0023] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0025] A method for preparing white high thermal conductivity para-aramid fiber, the preparation method comprising:

[0026] S1, dispersing hexagonal boron nitride in concentrated sulfuric acid to obtain a hexagonal boron nitride dispersion;

[0027] S2, dissolving poly(p-phenylene terephthalamide) in a hexagonal boron nitride dispersion to obtain a spinning solution;

[0028] S3, filtering and degassing the spinning solution, and then obtaining white high thermal conductivity para-aramid fiber through a spinning process.

[0029] Specifically, the particle size of the hexagonal boron nitride is 100-1000 nm.

[0030] Preferably, the particle size of the hexagonal boron nitride is 500-700 nm.

[0031] Specifically, in step S1, the weight ratio of the hexagonal boron nitride to the concentrated sulfuric acid is 1:(15-300); the mass concentration of the concentrated sulfuric acid is not less than 99.8% (the concentration calculated by converting sulfur trioxide in the concentrated sulfuric acid into sulfuric acid).

[0032] Preferably, in step S1, the weight ratio of hexagonal boron nitride to concentrated sulfuric acid is 1:(20-100).

[0033] Specifically, the weight ratio of the poly(p-phenylene terephthalamide) to the hexagonal boron nitride dispersion is 1:(3.9-4.3).

[0034] Specifically, the poly(p-phenylene terephthalamide) (PPTA) in the present invention is a polymer having an intrinsic viscosity (IV value) of 5-8 dL / g, which is prepared by a conventional low-temperature solution polycondensation reaction method of p-phenylene diamine and terephthaloyl chloride.

[0035] More specifically, the poly(p-phenylene terephthalamide) used in the embodiments of the present invention is a polymer having an intrinsic viscosity (IV value) of 7 dL / g.

[0036] Specifically, hexagonal boron nitride is dispersed in concentrated sulfuric acid by a high-speed shear emulsifier, the speed of the high-speed shear emulsifier is 2000-3000rpm, the emulsification time is 2-5h, and after emulsification, poly(p-phenylene terephthalamide) and hexagonal boron nitride dispersion liquid are immediately mixed by a twin-screw extruder to prepare a spinning solution. This is to avoid the hexagonal boron nitride dispersed in the hexagonal boron nitride dispersion liquid from stratification and re-agglomeration.

[0037] Specifically, the specific process of step S3 is: filtering and degassing the spinning solution, extruding it through a spinneret for dry-jet wet spinning, alkali washing, water washing, drying, and oiling to obtain white high thermal conductivity para-aramid fiber.

[0038] More specifically, the specific conditions of the dry-wet spinning process used in the embodiment of the present invention are as follows: after filtering and degassing the spinning solution, the slurry is extruded through the spinneret, the slurry passes through an 8 mm air layer, enters the coagulation bath, and then passes through the coagulation tube in the center of the coagulation tank and flows out from under the coagulation tube, wherein the coagulation bath temperature is 10°C, and the coagulation bath is a sulfuric acid aqueous solution with a mass concentration of 5%; finally, white high thermal conductivity para-aramid fiber is obtained through alkali washing, water washing, drying, and oiling, wherein the drying temperature is 120°C.

[0039] Specifically, the diameter of the spinneret hole is 0.05-0.1 mm; an aqueous sodium hydroxide solution with a mass concentration of 0.1-4% is used for alkali washing; and the water washing is multi-stage water washing with deionized water until the para-aramid fiber is neutral.

[0040] A white high thermal conductivity para-aramid fiber, the white high thermal conductivity para-aramid fiber is prepared by the preparation method of the present invention. The white high thermal conductivity para-aramid fiber has a single fiber fineness of 1.5D, a multifilament linear density of 400-3000D, and a thermal conductivity along the fiber axis of 0.1 W / (m·K) or more.

[0041] Example 1

[0042] 1 kg of hexagonal boron nitride powder with a particle size of 500 nm and 300 kg of 100% concentrated sulfuric acid were added to a high-speed shear emulsifier, the speed of the emulsifier was 2000 rpm, and emulsification was performed for 2 hours to obtain a hexagonal boron nitride dispersion.

[0043] Weigh 72 kg of poly(p-phenylene terephthalamide), dissolve the poly(p-phenylene terephthalamide) in the above-obtained hexagonal boron nitride dispersion through a twin-screw extruder, and mix them evenly to obtain a spinning solution;

[0044] After the spinning solution is filtered and degassed, it is passed through a spinneret with a pore size of 0.07 mm and a hole number of 1000 for dry-jet wet spinning, and then alkali washed (2% sodium hydroxide aqueous solution), washed with water, dried and heat treated to obtain white high thermal conductivity para-aramid fiber.

[0045] Example 2

[0046] 1 kg of hexagonal boron nitride powder with a particle size of 700 nm and 300 kg of 100% concentrated sulfuric acid were added to a high-speed shear emulsifier, the speed of the emulsifier was 2000 rpm, and emulsification was performed for 2 hours to obtain a hexagonal boron nitride dispersion.

[0047] Weigh 72 kg of poly(p-phenylene terephthalamide), and dissolve the poly(p-phenylene terephthalamide) in the above-obtained hexagonal boron nitride dispersion through a twin-screw extruder to obtain a spinning solution;

[0048] After the spinning solution is filtered and degassed, it is passed through a spinneret with a pore size of 0.07 mm and a hole number of 1000 for dry-jet wet spinning, and then alkali washed (0.1% sodium hydroxide aqueous solution), washed with water, dried and heat treated to obtain white high thermal conductivity para-aramid fiber.

[0049] Example 3

[0050] 1 kg of hexagonal boron nitride powder with a particle size of 500 nm and 20 kg of 100% concentrated sulfuric acid were added to a high-speed shear emulsifier, the speed of the emulsifier was 2000 rpm, and emulsification was performed for 2 hours to obtain a hexagonal boron nitride dispersion.

[0051] Weigh 5 kg of poly(p-phenylene terephthalamide), and dissolve the poly(p-phenylene terephthalamide) in the above-obtained hexagonal boron nitride dispersion through a twin-screw extruder to obtain a spinning solution;

[0052] After the spinning solution is filtered and degassed, it is passed through a spinneret with a pore size of 0.07 mm and a hole number of 1000 for dry-jet wet spinning, and then alkali washed (4% sodium hydroxide aqueous solution), washed with water, dried and heat treated to obtain white high thermal conductivity para-aramid fiber.

[0053] Example 4

[0054] 1 kg of hexagonal boron nitride powder with a particle size of 600 nm and 100 kg of concentrated sulfuric acid with a concentration of 99.8% were added to a high-speed shear emulsifier, the speed of the emulsifier was 3000 rpm, and emulsification was performed for 3 hours to obtain a hexagonal boron nitride dispersion.

[0055] Weigh 25.8 kg of poly(p-phenylene terephthalamide), dissolve the poly(p-phenylene terephthalamide) in the above-obtained hexagonal boron nitride dispersion through a twin-screw extruder, and mix them evenly to obtain a spinning solution;

[0056] After the spinning solution is filtered and degassed, it is passed through a spinneret with a pore size of 0.07 mm and a hole number of 1000 for dry-jet wet spinning, and then alkali washed (2% sodium hydroxide aqueous solution), washed with water, dried and heat treated to obtain white high thermal conductivity para-aramid fiber.

[0057] Example 5

[0058] 1 kg of hexagonal boron nitride powder with a particle size of 100 nm and 15 kg of 100% concentrated sulfuric acid were added to a high-speed shear emulsifier, the speed of the emulsifier was 2000 rpm, and emulsification was performed for 5 hours to obtain a hexagonal boron nitride dispersion.

[0059] Weigh 3.73 kg of poly(p-phenylene terephthalamide), dissolve the poly(p-phenylene terephthalamide) in the above-obtained hexagonal boron nitride dispersion through a twin-screw extruder, and mix them evenly to obtain a spinning solution;

[0060] After the spinning solution is filtered and degassed, it is passed through a spinneret with a pore size of 0.07 mm and a hole number of 1000 for dry-jet wet spinning, and then alkali washed (2% sodium hydroxide aqueous solution), washed with water, dried and heat treated to obtain white high thermal conductivity para-aramid fiber.

[0061] Example 6

[0062] 1 kg of hexagonal boron nitride powder with a particle size of 1000 nm and 80 kg of 100% concentrated sulfuric acid were added to a high-speed shear emulsifier, the speed of the emulsifier was 3000 rpm, and emulsification was performed for 3 hours to obtain a hexagonal boron nitride dispersion.

[0063] Weigh 20 kg of poly(p-phenylene terephthalamide), dissolve the poly(p-phenylene terephthalamide) in the above-obtained hexagonal boron nitride dispersion through a twin-screw extruder, and mix them evenly to obtain a spinning solution;

[0064] After the spinning solution is filtered and degassed, it is passed through a spinneret with a pore size of 0.07 mm and a hole number of 1000 for dry-jet wet spinning, and then alkali washed (2% sodium hydroxide aqueous solution), washed with water, dried and heat treated to obtain white high thermal conductivity para-aramid fiber.

[0065] Comparative Example 1

[0066] 300 kg of 100% concentrated sulfuric acid and 72 kg of poly(p-phenylene terephthalamide) are extruded through a twin-screw extruder to dissolve the poly(p-phenylene terephthalamide) in concentrated sulfuric acid to obtain a spinning solution;

[0067] After the spinning solution is filtered and degassed, it is passed through a spinneret with a pore size of 0.07 mm and a hole number of 1000 for dry-jet wet spinning, and then alkali washed (2% sodium hydroxide aqueous solution), washed with water, dried and heat treated to obtain para-aramid fiber.

[0068] Comparative Example 2

[0069] The white high thermal conductivity para-aramid fiber was prepared by the same method as in Example 1, except that hexagonal boron nitride with a smaller particle size was used. The particle size of the hexagonal boron nitride powder used in this comparative example 2 was 50 nm. The specific preparation process is as follows:

[0070] 1 kg of hexagonal boron nitride powder with a particle size of 50 nm and 300 kg of 100% concentrated sulfuric acid were added to a high-speed shear emulsifier, the speed of the emulsifier was 2000 rpm, and emulsification was performed for 2 hours to obtain a hexagonal boron nitride dispersion.

[0071] Weigh 72 kg of poly(p-phenylene terephthalamide), dissolve the poly(p-phenylene terephthalamide) in the above-obtained hexagonal boron nitride dispersion through a twin-screw extruder, and mix them evenly to obtain a spinning solution;

[0072] After the spinning solution is filtered and degassed, it is passed through a spinneret with a pore size of 0.07 mm and a hole number of 1000 for dry-jet wet spinning, and then alkali washed (2% sodium hydroxide aqueous solution), washed with water, dried and heat treated to obtain white high thermal conductivity para-aramid fiber.

[0073] Comparative Example 3

[0074] The white high thermal conductivity para-aramid fiber was prepared by the same method as in Example 1, except that hexagonal boron nitride with a larger particle size was used. The particle size of the hexagonal boron nitride powder used in this comparative example 3 was 1200 nm. The specific preparation process is as follows:

[0075] 1 kg of hexagonal boron nitride powder with a particle size of 1200 nm and 300 kg of 100% concentrated sulfuric acid were added to a high-speed shear emulsifier, the speed of the emulsifier was 2000 rpm, and emulsification was performed for 2 hours to obtain a hexagonal boron nitride dispersion.

[0076] Weigh 72 kg of poly(p-phenylene terephthalamide), dissolve the poly(p-phenylene terephthalamide) in the above-obtained hexagonal boron nitride dispersion through a twin-screw extruder, and mix them evenly to obtain a spinning solution;

[0077] After the spinning solution is filtered and degassed, it is passed through a spinneret with a pore size of 0.07 mm and a hole number of 1000 for dry-jet wet spinning, and then alkali washed (2% sodium hydroxide aqueous solution), washed with water, dried and heat treated to obtain white high thermal conductivity para-aramid fiber.

[0078] The para-aramid fibers prepared in the above examples and comparative examples were tested for performance indicators, and the specific results are shown in Table 1. The test items involved and the equipment used are as follows:

[0079] (1) Linear density: yarn length measuring machine, the testing method refers to GB / T 1033.1-2008;

[0080] (2) Tensile strength: Instron universal electronic material testing machine, test method according to GB / T 19975-2005;

[0081] (3) Elongation at break: Instron universal electronic material testing machine, test method according to GB / T 19975-2005;

[0082] (4) Thermal conductivity: Planar thermal diffusion coefficient tester LW9514, the detection method refers to the Angstrom method, and the test is along the fiber axis.

[0083] (5) Color fastness to light: the test method refers to GB / T 8427-2019.

[0084] Table 1 Para-aramid fiber performance data

[0085]

[0086] From the data in Table 1, it can be seen that the color of the para-aramid fibers obtained by the preparation method of the present invention in Examples 1-6 is white, the addition of hexagonal boron nitride improves the fiber strength, and the strength of the white para-aramid fibers obtained in Examples 1-6 is higher than that of the original color fibers in Comparative Example 1; the fiber elongation at break tends to decrease, but the change is not very obvious, and it can still meet the use standard requirements of para-aramid fibers; the thermal conductivity of the para-aramid fibers obtained by the preparation method of the present invention is above 0.1 W / (m·K), which is significantly improved compared with Comparative Example 1. In addition, the para-aramid fibers obtained by the preparation method of the present invention have good light fastness and are suitable for long-term use without discoloration.

[0087] From the data comparison of Comparative Example 2 and Example 1, it can be seen that if the particle size of hexagonal boron nitride is too small, the mechanical properties and thermal conductivity of the para-aramid fiber will decrease. In addition, it is found in the experiment that if hexagonal boron nitride with a smaller particle size is used, it is easy to cause the spinneret hole to be blocked during the spinning process, resulting in an unsmooth spinning process. Because hexagonal boron nitride with a too small particle size is used, the hexagonal boron nitride is easy to agglomerate, which eventually leads to the decrease of the mechanical properties and thermal conductivity of the para-aramid fiber, as well as the problem of spinneret hole blockage.

[0088] From the comparison of the data of Comparative Example 3 and Example 1, it can be seen that if the particle size of hexagonal boron nitride is too large, the mechanical properties and thermal conductivity of the para-aramid fiber will also decrease. In addition, it is found in the experiment that if hexagonal boron nitride with a larger particle size is used, it is easy to cause the spinneret hole to be blocked during the spinning process, resulting in an unsmooth spinning process. Therefore, the use of hexagonal boron nitride with a particle size defined by the present invention is more conducive to obtaining white high thermal conductivity para-aramid fiber with excellent performance.

[0089] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0090] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing white high thermal conductivity para-aramid fiber, characterized in that: The preparation method is: S1, dispersing hexagonal boron nitride in concentrated sulfuric acid to obtain a hexagonal boron nitride dispersion; S2, dissolving poly(p-phenylene terephthalamide) in a hexagonal boron nitride dispersion to obtain a spinning solution; S3, filtering and degassing the spinning solution, and then spinning the solution to obtain white high thermal conductivity para-aramid fiber; The particle size of the hexagonal boron nitride is 100-1000nm; In step S1, the weight ratio of the hexagonal boron nitride to the concentrated sulfuric acid is 1:(15-300); the mass concentration of the concentrated sulfuric acid is not less than 99.8%; The hexagonal boron nitride is dispersed in concentrated sulfuric acid by a high-speed shear emulsifier, the speed of the high-speed shear emulsifier is 2000-3000rpm, the emulsification time is 2-5h, and immediately after emulsification, the poly(p-phenylene terephthalamide) and the hexagonal boron nitride dispersion are mixed by a twin-screw extruder to obtain a spinning solution.

2. The method for preparing a white high thermal conductivity para-aramid fiber according to claim 1, characterized in that: The particle size of the hexagonal boron nitride is 500-700nm.

3. The method for preparing a white high thermal conductivity para-aramid fiber according to claim 1, characterized in that: In step S1, the weight ratio of hexagonal boron nitride to concentrated sulfuric acid is 1:(20-100).

4. The method for preparing a white high thermal conductivity para-aramid fiber according to claim 1, characterized in that: The weight ratio of the poly(p-phenylene terephthalamide) to the hexagonal boron nitride dispersion is 1:(3.9-4.3).

5. The method for preparing a white high thermal conductivity para-aramid fiber according to claim 1, characterized in that: The specific process of step S3 is: filtering and degassing the spinning solution, extruding it through a spinneret for dry-jet wet spinning, alkali washing, water washing, drying, and oiling to obtain white high thermal conductivity para-aramid fiber.

6. A white high thermal conductivity para-aramid fiber, characterized in that: The white high thermal conductivity para-aramid fiber is prepared by the preparation method described in any one of claims 1 to 5.

7. A white high thermal conductivity para-aramid fiber according to claim 6, characterized in that: The monofilament fineness of the white high thermal conductivity para-aramid fiber is 1.5D, the multifilament linear density is 400-3000D, and the thermal conductivity along the fiber axis is above 0.1 W / (m·K).

Citation Information

Patent Citations

  • Preparation method of colored para-position aramid fiber

    CN110359115A

  • Preparation method of colored para-aramid fiber and fiber product prepared by method

    CN113882030A

  • Dope-dyed p-aramid filament yarn and preparation method thereof

    CN103726124A